Silent Majority, Violent Majority: The Counter-Revolution in 70s Cinema - Peter Andrew Novick (Enthymema, 2012)
«There is one question, Inspector Callahan: Why do they call you ‘Dirty Harry’?» Harry, it is explained, «…Hates everybody: Limeys, Micks, Hebes, Fat Degos, Niggers, Honkies, Chinks…especially Spics». Don Siegel’s Dirty Harry (1971), famously labeled «fascist» by prominent film critic Pauline Kael, nonetheless represented something new and unique—the “Silent Majority’s” entry into liberal New Hollywood, a veritable counter-reformation to the new social movements having sprung up in the late Sixties and early Seventies. Far from the traditional American Right, however, and distinctly un-Fascist (in as much as the term means more than a simple epithet), these films acted to unite traditional European philosophy and revolutionary thought with organic conservative American tendencies, resulting in hybrid films which challenged the new social movements, while working within the medium of liberal New American Cinema. The article will address three themes from the era: violence and race in the city, revenge against “liberated women”, and fear and loathing of homosexuality. In each instance, using primary evidence from films and critical reviews from the Seventies and the present era, in addition to American and European theorists, the article will show how the counter-revolution in Seventies cinema failed to expunge the “revolutionary spirit” of the era. Rather, the Silent Majority’s visions of visual violence and reactionary values became part and parcel of the new liberated culture of the “Me Decade,” forever bounding the conservative celluloid revolt to the new cinematic culture.